Bacterial and Fungal Toll-Like Receptor Activation Elicits Type I IFN Responses in Mast Cells - Kornstädt, Lisa; Pierre, Sandra; Weigert, Andreas; Ebersberger, Stefanie; Schäufele, Tim J.; Kolbinger, Anja; Schmid, Tobias; Cohnen, Jennifer; Thomas, Dominique; Ferreirós, Nerea; Brüne, Bernhard; Ebersberger, Ingo; et al. (Frontiers in Immunology, 2021)
Next to their role in IgE-mediated allergic diseases and in promoting inflammation, mast cells also have antiinflammatory functions. They release pro- as well as antiinflammatory mediators, depending on the biological setting. Here we aimed to better understand the role of mast cells during the resolution phase of a local inflammation induced with the Toll-like receptor (TLR)-2 agonist zymosan. Multiple sequential immunohistology combined with a statistical neighborhood analysis showed that mast cells are located in a predominantly antiinflammatory microenvironment during resolution of inflammation and that mast cell-deficiency causes decreased efferocytosis in the resolution phase. Accordingly, FACS analysis showed decreased phagocytosis of zymosan and neutrophils by macrophages in mast cell-deficient mice. mRNA sequencing using zymosan-induced bone marrow-derived mast cells (BMMC) revealed a strong type I interferon (IFN) response, which is known to enhance phagocytosis by macrophages. Both, zymosan and lipopolysaccharides (LPS) induced IFN-β synthesis in BMMCs in similar amounts as in bone marrow derived macrophages. IFN-β was expressed by mast cells in paws from naïve mice and during zymosan-induced inflammation. As described for macrophages the release of type I IFNs from mast cells depended on TLR internalization and endosome acidification. In conclusion, mast cells are able to produce several mediators including IFN-β, which are alone or in combination with each other able to regulate the phagocytotic activity of macrophages during resolution of inflammation.